METODE DU PONT SYSTEM UNTUK MENILAI KINERJA KEUANGAN PADA PERUSAHAAN FOOD AND BAVERAGE YANG TERDAFTAR DI BEI PERIODE 2013-2016 - janio, indianies (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2018)
The purpose of this study was to determine the company's financial performance by usingthe method du pont system. This study uses financial statement data for the 2012-2015 period anduses the Du Pont System method with a focus on research on ROE which is influenced by EquityMultiplier, ROI influenced by Net Profit Margin and Total Turn Over Assets. The companies studiedwere three Food and Beverage Companies listed on the Stock Exchange, namely PT. Mayora Indah,PT. Three Pillars of Prosperity Tbk and PT. Indofood CBP Sukses Makmur Tbk. The results showedthat the return on investment resulting from the net profit margin, PT Indofood CBP Sukses MakmurTbk had a fairly stable return on investment every year even though it had experienced a decline in2013 and 2014 but experienced a return and obtained the largest percentage of net profit margin inthe year 2015 compared to two other companies. Fluctuations in return on investment or ROI areinfluenced by many factors, such as net profit margins and total assets turnover. The net profit marginis derived from net profit (loss) divided by sales in each period, so that the net profit margin is affectedby the amount of sales, cost of goods sold, operating expenses which consist of sales expenses andgeneral and administrative expenses and other net expenses incurred in order to generate net incomein each period. Total assets turnover is also a factor that influences the rate of return on investmentROI obtained from sales divided by the total assets of the company each period. So that the totalassets turnover is influenced by the amount of assets owned by the company which consists of currentassets and non-current assets whose values differ in each period. Judging from the percentage ofROA generated from this study, PT Mayora Indah Tbk was able to produce the highest ROA and wasa very significant increase compared to the ROA generated in the previous year, because the resultswere almost twice the ROA of the previous year. PT Mayora Indah Tbk's Return On Equity is alsoconsidered good because of the highest ROE in each year compared to PT Tiga Pilar Sejahtera Tbkand PT Indofood CBP Sukses Makmur Tbk.